Inhibition of the different complement pathways has varying impacts on the serum bactericidal activity and opsonophagocytosis against Haemophilus influenzae type b - Muri, Lukas; Schubart, Anna; Thorburn, Christine; Zamurovic, Natasa; Holbro, Thomas; Kammüller, Michael; Pluschke, Gerd; Ispasanie, Emma (Frontiers in Immunology, 2022)
Defense against Haemophilus influenzae type b (Hib) is dependent on antibodies and complement, which mediate both serum bactericidal activity (SBA) and opsonophagocytosis. Here we evaluated the influence of capsule-specific antibodies and complement inhibitors targeting the central component C3, the alternative pathway (AP; fB, fD), the lectin pathway (LP; MASP-2) and the terminal pathway (C5) on both effector functions. Findings may be relevant for the treatment of certain diseases caused by dysregulation of the complement system, where inhibitors of complement factors C3 or C5 are used. Inhibitors against other complement components are being evaluated as potential alternative treatment options that may carry a reduced risk of infection by encapsulated bacteria. Serum and reconstituted blood of healthy adults were tested for bactericidal activity before and after vaccination with the Hib capsule-conjugate vaccine ActHIB. Most sera had bactericidal activity prior to vaccination, but vaccine-induced antibodies enhanced SBA titers significantly. Independently of the vaccination status, both C3 and C5 inhibition abrogated SBA, whereas inhibition of the LP had no effect. AP inhibition had a major inhibitory effect on SBA of pre-immunization serum, but vaccination mitigated this inhibition for all disease isolates tested. Despite this, SBA-mediated killing of some Hib isolates remained retarded. Even for the most serum-resistant isolate, SBA was the dominating defense mechanism in reconstituted whole blood, as addition of blood cells to the serum did not enhance bacterial killing. Limited Fc receptor-mediated opsonophagocytosis was unmasked when bacterial killing by the membrane attack complex was blocked. In the presence of C3 or C5 inhibitors, addition of post-immunization, but not of pre-immunization serum to the blood cells triggered opsonophagocytosis, leading to suppression of bacterial multiplication. Taken together, our data indicate that for host defense against Hib, killing by SBA is more efficient than by blood cell opsonophagocytosis. However, additional defense mechanisms, such as bacterial clearance by spleen and liver, may play an important role in preventing Hib-mediated sepsis, in particular for Hib isolates with increased serum-resistance. Results indicate potentially improved safety profile of AP inhibitors over C3 and C5 inhibitors as alternative therapeutic agents in patients that could be more susceptible to Hib infection.